2017
DOI: 10.1186/s40814-017-0133-z
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of high-intensity interval training and moderate-intensity continuous training in adults with inactive or mildly active Crohn’s disease: study protocol for a randomised controlled trial

Abstract: BackgroundStructured exercise training has been proposed as a useful adjunctive therapy for Crohn’s disease by improving immune function and psychological health, reducing fatigue and promoting gains in muscle and bone strength. However, the evidence for exercise in Crohn’s disease is sparse, with only a handful of small prospective trials [1, 2], with methodological limitations, including the use of non-randomised and non-controlled study designs and small sample sizes. Here, we describe the protocol for a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…A full description of the methods has been published [19]. The study was a multi-centre, three-arm, parallel-group, pilot randomised controlled trial.…”
Section: Methodsmentioning
confidence: 99%
“…A full description of the methods has been published [19]. The study was a multi-centre, three-arm, parallel-group, pilot randomised controlled trial.…”
Section: Methodsmentioning
confidence: 99%
“…217 A trial assessing two exercise regimens in adults with inactive or mildly active CD is currently underway. 218 New technology, including nextgeneration wearable physical activity trackers, could potentially improve exercise studies and might be used to promote physical activity 219 in IBD patients.…”
Section: Exercise Current Practice Position 53mentioning
confidence: 99%
“…A number of studies have confirmed the improved psychometric properties of the 5L in both general population and patient samples, including cancer, chronic hepatic diseases, diabetes, osteoarthritis, psoriasis and stroke [29]. No studies have reported on HRQoL in patients with CD as assessed by the 5L, and only two published clinical trial protocols, planning to use the 5L questionnaire in CD patients, are present [30,31]. Nevertheless, as of the time this manuscript was written, results…”
Section: Introductionmentioning
confidence: 96%